2006
DOI: 10.1074/jbc.m600933200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ser-129 Is the Dominant Pathological Modification of α-Synuclein in Familial and Sporadic Lewy Body Disease

Abstract: A comprehensive, unbiased inventory of synuclein forms present in Lewy bodies from patients with dementia with Lewy bodies was carried out using two-dimensional immunoblot analysis, novel sandwich enzyme-linked immunosorbent assays with modification-specific synuclein antibodies, and mass spectroscopy. The predominant modification of ␣-synuclein in Lewy bodies is a single phosphorylation at Ser-129. In addition, there is a set of characteristic modifications that are present to a lesser extent, including ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
1,298
5
24

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,202 publications
(1,429 citation statements)
references
References 35 publications
51
1,298
5
24
Order By: Relevance
“…Phosphorylation of αS at S129 is the most abundant posttranslational modification in Lewy bodies (Anderson et al, 2006;Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of αS at S129 is the most abundant posttranslational modification in Lewy bodies (Anderson et al, 2006;Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…4A) is the most abundant post-translational modification of αS in PD (Anderson et al, 2006;Fujiwara et al, 2002). Titration of pS129-αS to Rab8a(GDP) revealed that, at the same molar ratio, Rab8a caused stronger NMR signal attenuation in pS129-αS than in wild-type αS (Figs.…”
Section: αS Interacts With Rab8a In Rodent Brainmentioning
confidence: 99%
“…3 They found the protein to have a molecular mass consistent with the presence of an additional acetyl group, 3 and it has been known for several years that AS purified from both normal and pathological brain tissue is N-terminally acetylated. 5 Wang et al purified from E. coli an AS construct that included an additional 10 residue N-terminal fragment 4 which may mimic the physical consequences of N-terminal acetylation. Both manuscripts suggested that the mild, non-denaturing conditions used for purification may also preserve the native tetramer structure.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation at Ser-129 is a specific marker of all ␣-synucleinopathy lesions including PD (16). Alteration of Ser-129 to the negatively charged aspartate to mimicphosphorylationandSer-129phosphorylationbyGprotein-coupled receptor kinase 2 significantly enhanced ␣-syn toxicity in the Drosophila model of Parkinson disease (17).…”
mentioning
confidence: 99%